EFFECT OF PRIVATE TUTORING ON SELF-CONFIDENCE AMONG SECONDARY SCHOOL STUDENTS - Kaur, Ms. Manpreet (International Journal of Psychosocial Rehabilitation, 2020)
The sector of private tutoring is expanding rapidly, as the competitive era demands extra efforts to achieve the aims of life and education. Most of the students feel uneasy and uncomfortable in facing challenges as they lack in self-confidence because of less encouragement and lack of right guidance. Schools are also becoming a part of race only and they cannot attend each and every student individually. Parents are also busy in their work and don’t have enough time to motivate their children, so they arrange private tutoring for them. So keeping this view in mind, the researcher found if there is any effect of private tutoring on self-confidence among students. For this study, descriptive survey method of research was adopted and 100 secondary school students (50 female & 50 male) were selected randomly for data collection through personal interview and selfconfidence inventory (2007) by D.D. Pandey to assess self-confidence among secondary school students. Descriptive statistics and t-test were employed to analyze and interpret the data. Results revealed that school students perceive average self-confidence and there is significant difference between the self-confidence of school students who were taking and not taking private tutoring. Further, private tutoring taking school students have better self-confidence than school students who were not taking private tutoring, but there is no difference between the self-confidence of male and female school students who were taking private tutoring. Suggestions and recommendations were made for further research.